水都大阪 水都再生という壮大な社会実験と新たな都市像 - Kana Koichi 嘉名光市 (Projets de Paysage)
Water cities are characterised by an interface with water, as in the case of Venice and San Antonio. These cities have profound ties with their banks and shores, and each city has an illustrious past. Osaka, the second-largest city in Japan, is one such city. Despite its long history, it has changed in appearance a great deal since the 19th century. Means of transport have evolved from fluvial to land transport, high tides have caused repeated damage, land subsidence has worsened, water quality has deteriorated due to the influx of domestic sewage, and the illegal occupation of land has increased. In addition to all these factors, motorisation and the construction of dikes, referred to as "razor dikes", to control water have transformed the riverbanks into forgotten areas no longer frequented. Recent attempts have been made to regenerate the city of Osaka by starting from its riverbanks. The Prefecture and the Town Hall of Osaka as well as the local business community have been working together since 2001 to revitalise the city as a water city. One of the approaches adopted to transform Osaka into a "aquatic metropolis", has been inspired by a new urban vision of the riverbanks which encompasses a deregulation of fluvial law.